The Role of Regulators in Strengthening Pentahelix Collaboration For Islamic Philanthropy Management in Indonesia - Neneng Nurhasanah; Muhammad Rifqi Fathurrahman; Nandang Ihwanuddin; Udin Saripudin; Junaidah Abu Seman; Muhammad Ridha Taufik Rahman; Nur Efendi; Irvan Nugraha; Sidik Ramdhan Arrasyid; Salma Nurul Fadhilah (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025